Analisis Implementasi Kesehatan Dan Keselamatan Kerja di Rumah Sakit (K3RS) Menggunakan Metode PDCA (Plan-Do-Check-Act) di RSUD DR.Moewardi Surakarta - Indriyani, Yeni, Tarwaka, PGDip, Sc, M.Eng, Kusuma Estu Werdani, SKM, M.Kes (2016)
K3RS is done by the continuing process by applying PDCA (PlanDo-Check-Act). The purpose of this research is to find out the description of the program implementation of OHS in hospital by using PDCA (Plan-Do-Check-Act) method in Dr. Moewardi Regional Hospital Surakarta. The type of this research is descriptive approach of fenomenal transcendent study by interviewing in-depth toward 5 informants: chief, secretary, and member of P2K3. Based on the result of this research from the stage of planning (Plan), implementation (Do), monitoring and evaluating (Check), and follow up plan (Act), 5 informants state that K3RS in Regional Hospital has run well but it has not been maximal. Suggestion for the hospital is to appoint professional labor of K3 or their member that has K3 education background and must audit SMK3 once in three years.